ChemInform Abstract: Brownmillerite Ca2Co2O5: Synthesis, Stability, and Re‐entrant Single Crystal to Single Crystal Structural Transitions. Issue 10 (March 2015) - Zhang, Junjie; Zheng, Hong; Malliakas, Christos D.; Allred, Jared M.; Ren, Yang; Li, Qing'an; Han, Tian‐Heng; Mitchell, J. F.
Abstract Ca2Co2O5 is prepared by calcination of a stoichiometric mixture of CaCO3 and Co3O4 in O2 (Pt crucible, 900 °C, 1 d) followed by sintering (1000 °C, 1 d).